Efektivitas Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Di Desa Banjarsari Kecamatan Sukatani Kabupaten Bekasi Tahun 2017-2023 - Dahuri, Adin; Yani, Yani (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The research is descriptive with qualitative approach. The research concerns on the collection effectiveness of Land and Building of Rural and Urban Tax (PBB-P2) of Banjarsari Sub District in 2017-2023. Data of tax achievement obtained from Departmen of Tax in Sukatani District and information relating to the research collected by interviewing tax collector as well as some residents of Banjarsari Sub Dictrict of Bekasi Regency. The result of the reseach that the achievement of PBB-P2 revenue during 2017-2023 ranged from 35% to 67% or an average achievement of 46,86% per year. These achievements showed that the efforts to collect PBB-P2 revenue during that period were ineffective because the realization of PBB-P2 revenues did not reach predetermined targets. The ineffectiveness PBB-P2 collection is due to some obsracles, such as the obedience of some tax payers which continuosly to be encouraged, lack of officers which being very disproportionate to the number of tax payers, as well as ineffective the use of